Dietary therapies for eosinophilic esophagitis. (2014) - Arias, Ángel; Lucendo, Alfredo J
Abstract : Eosinophilic esophagitis (EoE) represents a prevalent chronic esophageal disorder. Since the condition was first described, its pathophysiology has been known to have an immune-allergic origin, but the high response rate to dietary therapies based on feeding patients exclusively with amino acid-based elemental formulas (with complete elimination of table foods) has clearly established EoE as a particular form of food allergy. Nevertheless, the management of EoE in clinical practice remains widely heterogeneous, with topical steroids being a therapeutic mainstay. However, a growing body of evidence points to dietary therapy as an effective treatment option for both children and adults with EoE, as this approach is capable of achieving a sustained symptomatic and histological response without resorting to drugs. This article reviews the available data on the major types of dietary therapy for EoE, including elemental formula diets, skin allergy testing-directed elimination diets and empirical elimination diets based on common food allergens.